The war in the nest - Arcidiacono, Caterina; Ferrari Bravo, Gabriella (La camera blu. Rivista di studi di genere, 2015)
The article deals with the topic of domestic violence against women by describing the current state of affairs of the Italian social and cultural context as well as the dangerous influence of media and the actions of the welfare system. The need of disclosure and protection of the women victims of violence is also enlightened. A further aim of this contribution is to discuss some principles for the clinical and therapeutic listening and treatment directed to services and shelters since this form of violence is generally underestimated, silenced, and denied. It finally introduces some principles of institutional mediation and re-negotiation of emotional bonds that refer to the Neapolitan Centro per le Famiglie’s experience.